Odpowiedź :
Odpowiedź:
a) 4x + 5 = 2x – 7 | +7
4x +12 = 2x | -4x
12= -2x | : (-2)
-6 = x
b) -3x +8 = 2x + 7 | +3x
8 = 5x +7 | -7
1 = 5x | :5
0,2 = x
c) 3(y+ 2) = -2(y - 3)
3y + 6 = -2y +6 | -3y
6= y + 6 | -6
0 = y
d) 3x -7 = 27x + 11 | -11
3x - 18 = 27x | -3x
-18 = 24x | : 24
-0,75 = x
e) 8 - 3x² = 3x *(2 - x) -2x
8 - 3x² = 6x - 3x² -2x | +3x²
8 = 4x | :4
2 = x
f) (x+3)(x−4)=(x+2)(−1)
(−4)+3(−4)=(+2)(−1)
2−4+3(−4)=(+2)(−1)
2−4+3−12=(+2)(−1)
2−−12=(+2)(−1)
2−−12=(−1)+2(−1)
2−−12=2−+2(−1)
2−−12=2−+2−2
2−−12=2+1−2
Rozwiązanie:
2−−12=2+−2